The Corporate Governance Moderates Determinants Affecting Sustainability Report Disclosure - Herlina Lusmeida; Sarah Vanessa Amelia (Jurnal Akuntansi, 2023)
This research aims to gather empirical evidence on how profitability and leverage affect sustainability report disclosure while considering the moderating variables of independent commissioners and gender diversity on the board of directors. The study included 45 companies from the manufacturing, mining, property, real estate, and building construction industries listed on the IDX from 2019 to 2021, chosen through purposive sampling. The research data was analyzed using multiple regression analysis methods. According to the findings, profitability favours sustainability report disclosure, while leverage has a negative influence. The presence of independent commissioners does not moderate the relationship between profitability, leverage, and sustainability report disclosure. Although gender diversity on the board of directors does not significantly impact the relationship between profitability and sustainability report disclosure, it does reduce the negative impact of leverage on sustainability report disclosure.